Kingdom of the Netherlands : Aruba: 2013 Article IV Consultation: Staff Report, Informational Annex, Press Release. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that economic output in Aruba remains 12 percent below its pre-crisis level, with recovery slower than others in the Caribbean region. The non-oil current account (CA) balance, which mostly reflects developments in the tourism sector, has improved since mid-2000 reaching a balanced position in 2012. The overall CA balance, however, after being in surplus for years, showed volatilities in recent years reflecting oil-sector developments. In 2012, it recorded a surplus of 5 percent of GDP. In 2013, real output is projected to grow by 1u percent. Robust tourism growth and some pickup in consumption from projected deflation will support the subdued near-term recovery.